Cross-Reactive Results in Serological Tests for Borreliosis in Patients with Active Viral Infections - Iwona Wojciechowska-Koszko; Paweł Kwiatkowski; Monika Sienkiewicz; Mateusz Kowalczyk; Edward Kowalczyk; Barbara Dołęgowska (Pathogens, 2022)
Currently, serological tests for Lyme disease (LD), routinely performed in laboratories following the European Concerted Action on Lyme Borreliosis recommendations as part of two-stage diagnostics, are often difficult to interpret. This concerns both the generation of false positive and negative results, which frequently delay the correct diagnosis and implementation of appropriate treatment. The above problems result from both morphological and antigenic variability characteristics for the life strategy of the spirochete Borrelia burgdorferi sensu lato, a complicated immune response, and imperfections in diagnostic methods. The study aimed to check the reactivity of sera from 69 patients with confirmed infection with Epstein–Barr virus (EBV), cytomegalovirus (CMV) and BK virus (BKV) with Borrelia antigens used in serological tests: indirect immunofluorescence (IIFT), enzyme-linked immunosorbent (ELISA) and immunoblot (IB). In the group of patients infected with EBV, the highest percentage of positive/borderline anti-Borrelia IgM and IgG results was obtained in the following tests: IIFT (51.9% for IgM, 63.0% for IgG), ELISA (22.2% for IgM, 29.6% for IgG) and IB (11.1% for IgM, 7.4% for IgG). In the group of CMV-infected patients, the highest percentage of positive/borderline anti-Borrelia IgM results were obtained in the following tests: IB (23.1%), IIFT (15.4%) and ELISA (7.7%), while in the IgG class in the IIFT (15.4%), IB (11.5%) and ELISA (3.9%) tests. In the group of patients infected with BKV, the highest percentage of positive/borderline anti-Borrelia IgM results was obtained in the following tests: IIFT (25.0%), IB (25.0%) and ELISA (3.9%), and in the IgG class in the tests: IB (50.0%), IIFT (6.2%) and ELISA (6.2%). The native flagellin (p41) and OspC proteins were the most frequently detected Borrelia antigens in all studied groups of patients in both classes of antibodies. Similar to other authors, the study confirmed the fact that serological tests used in the diagnosis of LD have a high potential to generate false positive results in patients with active viral infections, which may be related to cross-reacting antibodies appearing during the most common polyclonal activation of T/B lymphocytes, activated by viral superantigens.